Production Guide for Choy Sum—An Emerging Asian Vegetable in Florida - Yanlin Wang; Guodong Liu (EDIS, 2020)
Choy sum, also known as Chinese flowering cabbage, is a leafy vegetable that has been widely cultivated in southern China for more than 1,000 years, and is currently cultivated and consumed by a growing population in the western world. This new 5-page publication of the UF/IFAS Horticultural Sciences Department, written by Yanlin Wang and Guodong Liu, provides a brief overview of choy sum and its cultivation, as well as some suggestions for how to include it in a meal. https://edis.ifas.ufl.edu/hs1380